Fire in Savannas and its Impact on Avifauna: Considerations for a Better Environmental Conservation - Nunes, Bárbara Beatriz da Silva (Sociedade & Natureza, 2023)
Savannas are a pyrophytic biome, a biodiversity hotspot, and have global importance, occupying 20% of the Earth's surface. It is a biome that requires burning to maintain its biodiversity and pyrodiversity. It has suffered from altered fire regimes due to the direct and indirect action of factors such as deforestation, agriculture, cattle ranching, and climate change, resulting in habitat loss, degradation, and fragmentation. This fact can impact the avifauna, changing population dynamics and distribution in the landscape. Thus, through a literature search, this study evaluated the influences of fire on avifauna populations in savannas. It was found that fire impacts avifauna directly or indirectly and acts positively or negatively, according to the niche of the species evaluated and its intrinsic characteristics. The observed effect will depend on the fire detection ability, locomotion capacity, species, habit, functional guild, demographic parameters, resource availability, post-disturbance successional evolution, dispersal ability, and the geographic scale of the area affected by the fire. The main impacts observed for this clade are indirect effects, and its most negatively impacted populations are the ratites and those with poor locomotion ability. Despite the many gaps in knowledge about the impact of fire on the population parameters of avifauna, studies that focus on community dynamics indicate that, in general, there are few changes in richness and abundance indices. Thus, a greater understanding of the consequences of fire on birds is necessary to support better the actions of the Integrated Fire Management Program and its expansion throughout the Brazilian territory in search of quality, dynamic, and integrated environmental management.